S-type heterojunction photocatalytic composite material as well as preparation method and application thereof

By using the S-shaped heterojunction photocatalytic composite formed by composite of porous ceria, gold and Prussian blue analogs, the problem of low catalytic activity in biomass photorefining is solved, the photocatalytic activity and carrier mobility are significantly improved, and the efficient conversion of corn stalks to formic acid is achieved.

CN119838635APending Publication Date: 2025-04-18NORTHEAST FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510003200.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, ceria has low catalytic activity in biomass photorefining due to its wide bandgap and low carrier migration efficiency, which in turn makes the conversion of photorefined corn stalks into high value-added platform compounds (such as formic acid) low conversion rate.

Method used

The S-shaped heterojunction photocatalytic composite material formed by composite of porous ceria, gold and Prussian blue analogs provides active sites through the porous structure, gold accelerates electron transfer, and the Prussian blue analog matches the bandgap structure with ceria, promoting charge transfer and redox capabilities.

Benefits of technology

The photocatalytic activity is significantly improved, the carrier mobility and the catalyst redox capacity are enhanced, and the yield and C atom conversion rate of corn stalks are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005226053220000011
    Figure HDA0005226053220000011
  • Figure HDA0005226053220000012
    Figure HDA0005226053220000012
  • Figure HDA0005226053220000013
    Figure HDA0005226053220000013
Patent Text Reader

Abstract

The invention provides an S-type heterojunction photocatalytic composite material as well as a preparation method and application thereof, and belongs to the technical field of composite materials. The photocatalytic composite material is constructed by adopting porous cerium dioxide, and rich active sites can be provided due to the porosity of the photocatalytic composite material; according to the invention, PBA is utilized to construct the photocatalytic composite material, so that charge of PBA can be effectively promoted to be transferred to cerium dioxide, the carrier mobility is improved, and the oxidation-reduction capacity of the catalyst is improved to the greatest extent; according to the invention, gold is adopted to construct the photocatalytic composite material, and the gold can accelerate electron transfer and improve the separation rate of electron holes, so that the photocatalytic activity of photocatalysis is improved. The S-shaped heterojunction of the photocatalytic composite material provided by the invention accelerates the carrier migration efficiency, improves the oxidation-reduction ability of a photocatalyst, and can realize that the catalytic material can simultaneously maintain the strong oxidation ability of electrons and the strong reduction ability of holes, so that the problems of wide band gap and low carrier migration efficiency of traditional cerium dioxide are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to an S-type heterojunction photocatalytic composite material and a preparation method and application thereof. Background Art

[0002] With the development of society, the use of fossil fuels still dominates. However, fossil fuels are non-renewable energy sources. Their excessive use will not only lead to an increasingly severe energy crisis, but also produce a large amount of carbon dioxide when burning fossil fuels, leading to environmental pollution. Therefore, research on renewable energy is very necessary. Solar energy and biomass resources are considered to be clean and sustainable renewable energy sources. Using solar energy to convert biomass resources to produce high value-added chemicals can reduce dependence on fossil energy and carbon emissions, and is an ideal way to refine biomass.

[0003] Corn stalks are a type of biomass waste that is usually treated by incineration, but this treatment method can cause serious environmental pollution problems such as smog and acid rain. The main components of corn stalks include cellulose (30-40%), hemicellulose (20-30%), and lignin (15-30%), and have the potential to be converted into high-value-added chemicals and biofuels. Among the downstream oxidation products of corn stalks, formic acid has the advantages of being non-toxic and non-flammable, and is widely used in fuel cells and biorefining. Therefore, if corn stalks can be photorefined and converted into formic acid, it will contribute to the sustainable resource development and utilization of corn stalks.

[0004] Among many photocatalysts, cerium dioxide (CeO2) is used in biomass photorefining due to its advantages such as hydrogen storage capacity and controllable morphology. However, the wide band gap energy (2.6eV) of CeO2 and its inability to retain the redox ability of holes and electrons at the same time limit the further application of CeO2, resulting in low catalytic activity when CeO2 is directly used in biomass photorefining, which in turn leads to low conversion rate of photorefined corn stover into high value-added platform compounds (such as formic acid). Summary of the invention

[0005] The object of the present invention is to provide an S-type heterojunction photocatalytic composite material and a preparation method and application thereof. The S-type heterojunction photocatalytic composite material provided by the present invention has excellent photocatalytic activity.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The invention provides an S-type heterojunction photocatalytic composite material. The photocatalytic composite material is an S-type heterojunction formed by a composite of porous cerium dioxide, gold and a Prussian blue analogue.

[0008] The present invention also provides a method for preparing the photocatalytic composite material described in the above technical solution, comprising the following steps:

[0009] (1) mixing porous cerium dioxide, a gold salt solution and a reducing agent, and performing a reduction reaction to obtain a porous cerium dioxide / gold composite material;

[0010] (2) mixing the porous cerium dioxide / gold composite material obtained in step (1) with a nickel salt solution to obtain a suspension;

[0011] (3) dissolving potassium cobalt cyanide and a surfactant in water to obtain a potassium cobalt cyanide mixed solution;

[0012] (4) The suspension obtained in step (2) is mixed with the potassium cobalt cyanide mixed solution obtained in step (3), and then subjected to aging treatment to obtain an S-type heterojunction photocatalytic composite material.

[0013] Preferably, the method for preparing porous cerium dioxide in step (1) comprises:

[0014] 1) mixing water, methyl methacrylate and an initiator to carry out a polymerization reaction to obtain polymethyl methacrylate;

[0015] 2) mixing Planck F-127, citric acid, a soluble cerium salt and a solvent to obtain an impregnation solution;

[0016] 3) mixing the polymethyl methacrylate obtained in step 1) with the impregnation solution obtained in step 2), and sequentially performing impregnation and drying to obtain a precursor;

[0017] 4) calcining the precursor obtained in step 3) to obtain porous cerium dioxide.

[0018] Preferably, the molar percentage of the gold salt solution in step (1) is 0.1-1%.

[0019] Preferably, the temperature of the reduction reaction in step (1) is room temperature, and the time of the reduction reaction is 0.5 to 3 hours.

[0020] Preferably, the molar percentage of the nickel salt solution in step (2) is 10-90%.

[0021] Preferably, in step (3), the mass ratio of potassium cobalt cyanide to surfactant is (0.1-3): (0.2-3).

[0022] Preferably, the temperature of the aging treatment in step (4) is room temperature.

[0023] Preferably, the aging treatment time is 1 to 24 hours.

[0024] The present invention also provides the use of the S-type heterojunction photocatalytic composite material described in the above technical solution or the S-type heterojunction photocatalytic composite material prepared by the preparation method described in the above technical solution as a biomass photorefining catalyst.

[0025] The present invention provides an S-type heterojunction photocatalytic composite material, wherein the S-type heterojunction photocatalytic composite material is an S-type heterojunction formed by a composite of porous cerium dioxide, gold and a Prussian blue analog. The present invention uses porous cerium dioxide to construct a photocatalytic composite material, and its porosity can provide abundant active sites and improve the catalytic activity of the photocatalyst; the present invention uses a Prussian blue analog to construct a photocatalytic composite material, and its band gap structure matches that of cerium dioxide (-0.52 to 1.87V), so cerium dioxide and a Prussian blue analog are combined and a heterostructure is constructed, which can effectively promote the charge transfer of the Prussian blue analog to cerium dioxide, improve the carrier mobility, and maximize the redox ability of the catalyst; the present invention uses gold to construct a photocatalytic composite material, and gold can accelerate electron transfer, increase the separation rate of electron holes, and thus improve the catalytic activity of photocatalysis. The photocatalytic composite material provided by the present invention is an S-type heterojunction formed by a composite of porous cerium dioxide, gold and Prussian blue analogs. The S-type heterojunction accelerates the efficiency of carrier migration and improves the redox ability of the photocatalyst. It can achieve that the catalytic material retains the strong oxidation ability of electrons and the strong reduction ability of holes at the same time, so as to solve the problem of the wide band gap and low carrier migration efficiency of traditional cerium dioxide. The results of the embodiment show that the yield of formic acid from light-refined straw provided by the S-type heterojunction photocatalytic composite material of the present invention is 19.6mmol L -1 , the C atom conversion rate of straw is 36.0%, which is 1.8 times that of pure cerium dioxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 XRD diagram of the S-type heterojunction photocatalytic composite material prepared in Examples 2 to 5 of the present invention;

[0027] Figure 2 UV-visible spectrophotometric curves of CeO2, CeO2 / Au and CeO2 / Au / 70% PBA prepared in Example 1 of the present invention;

[0028] Figure 3 The NH3-programmed temperature desorption test results of the S-type heterojunction photocatalytic composite material prepared in Example 1 of the present invention;

[0029] Figure 4 XRD patterns of CeO2 / Au / PBA and CeO2 / Au prepared in Example 1 of the present invention and CeO2 prepared in Comparative Example 1;

[0030] Figure 5The XRD patterns of the samples obtained in Examples 6 to 10 of the present invention and Comparative Example 1 are shown;

[0031] Figure 6 This is the SEM image of the sample obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The invention provides an S-type heterojunction photocatalytic composite material. The S-type heterojunction photocatalytic composite material is an S-type heterojunction formed by a composite of porous cerium dioxide, gold and a Prussian blue analogue.

[0033] In the present invention, the average pore size of the porous cerium dioxide is preferably 50 to 500 nm, more preferably 100 nm. In the present invention, the porous cerium dioxide is preferably three-dimensional ordered porous cerium dioxide. In the present invention, the porous cerium dioxide can provide a larger specific surface area for the S-type heterojunction photocatalytic composite material, on the one hand, it can form more active sites, and on the other hand, the S-type heterojunction photocatalytic composite material has a larger contact area with the reaction raw materials when in use, thereby improving the photocatalytic activity.

[0034] In the present invention, the particle size of the gold is preferably 2 to 8 nm, more preferably 5 nm. When the particle size of the gold in the photocatalyst composite material provided by the present invention is within the above range, it is more conducive to uniform distribution in the photocatalyst composite material, accelerating electron transfer and increasing the separation rate of electron holes.

[0035] In the present invention, the chemical formula of the Prussian blue analog is preferably A2M[M'(CN)6], wherein A is an alkali metal ion or zeolite water, M and M' are independently transition metal ions, and the transition metal ions are preferably Fe, Co or Mn. In the present invention, the Prussian blue analog is a type of metal organic framework with a simple cubic structure, having a unique three-dimensional open metal framework structure and a high specific surface area, and these characteristics can increase the contact area of ​​the catalyst and the number of active sites. In addition, the valence band and conduction band of the Prussian blue analog match each other with those of ceria, and an electron hole transport layer is formed between the two, and the heterostructure promotes the generation of Bronsted acid sites.

[0036] The present invention also provides a method for preparing the S-type heterojunction photocatalytic composite material described in the above technical solution, comprising the following steps:

[0037] (1) mixing porous cerium dioxide, a gold salt solution and a reducing agent, and performing a reduction reaction to obtain a porous cerium dioxide / gold composite material;

[0038] (2) mixing the porous cerium dioxide / gold composite material obtained in step (1) with a nickel salt solution to obtain a suspension;

[0039] (3) dissolving potassium cobalt cyanide and a surfactant in water to obtain a potassium cobalt cyanide mixed solution;

[0040] (4) The suspension obtained in step (2) is mixed with the potassium cobalt cyanide mixed solution obtained in step (3), and then subjected to aging treatment to obtain an S-type heterojunction photocatalytic composite material.

[0041] The invention mixes porous cerium dioxide, a gold salt solution and a reducing agent, and performs a reduction reaction to obtain a porous cerium dioxide / gold composite material.

[0042] In the present invention, the method for preparing the porous cerium dioxide preferably comprises:

[0043] 1) mixing water, methyl methacrylate and an initiator to carry out a polymerization reaction to obtain polymethyl methacrylate;

[0044] 2) mixing Planck F-127, citric acid, a soluble cerium salt and a solvent to obtain an impregnation solution;

[0045] 3) mixing the polymethyl methacrylate obtained in step 1) with the impregnation solution obtained in step 2), and sequentially performing impregnation and drying to obtain a precursor;

[0046] 4) calcining the precursor obtained in step 3) to obtain porous cerium dioxide.

[0047] In the present invention, water, methyl methacrylate and an initiator are preferably mixed to carry out a polymerization reaction to obtain polymethyl methacrylate.

[0048] In the present invention, the water is preferably deionized water. The present invention utilizes water as the reaction medium for the polymerization reaction.

[0049] In the present invention, the methyl methacrylate is a monomer for synthesizing polymethyl methacrylate.

[0050] In the present invention, the volume ratio of water to methyl methacrylate is preferably (1-5): 1, more preferably 2: 1. The present invention controls the volume ratio of water to methyl methacrylate within the above range, which is more conducive to obtaining three-dimensional ordered porous cerium dioxide.

[0051] In the present invention, the initiator preferably includes potassium persulfate, dibenzoyl peroxide or azobisisobutyronitrile, and more preferably potassium persulfate. In the present invention, by adding an initiator, methyl methacrylate can generate free radicals, and the free radicals are connected to each other to form polymethyl methacrylate, and a monomer polymerization reaction occurs to obtain polymethyl methacrylate.

[0052] The present invention has no particular limitation on the amount of the initiator, which can be adjusted as needed. In the present invention, by adding the initiator, methyl methacrylate can be fully reacted to form polymethyl methacrylate.

[0053] In the present invention, the method of mixing water, methyl methacrylate and initiator is preferably: after water and methyl methacrylate are uniformly mixed in an argon atmosphere to obtain a mixed solution, the initiator is added to the mixed solution. In the present invention, the mixing temperature is preferably 50 to 80° C., more preferably 60 to 70° C. The present invention is more conducive to improving the orderliness of polymethyl methacrylate pores by adopting this method.

[0054] In the present invention, the polymerization reaction temperature is preferably 50-80°C, more preferably 60-70°C; the polymerization reaction time is preferably 80-100 min, more preferably 90 min. The present invention controls the polymerization reaction temperature and time within the above ranges to fully complete the polymerization reaction.

[0055] In the present invention, the polymerization reaction is preferably carried out under stirring, and the stirring speed is preferably 100 to 500 rmin -1 , more preferably 200 to 400 rmin -1 The present invention can make the polymerization reaction more complete through stirring and improve the uniformity of the pores of the polymerization reaction product.

[0056] In the present invention, after the polymerization reaction, the product of the polymerization reaction is preferably filtered, washed and dried in sequence to obtain polymethyl methacrylate. The present invention does not specifically limit the operation methods of the filtering, washing and drying, and conventional filtering, washing and drying methods can be used. In an embodiment of the present invention, the pore size of the filter paper used for the filtration may be 1 μm; the filtrate obtained by the filtration is centrifugally washed; the drying device may be an oven, the drying temperature may be 60°C, and the drying time may be 12 hours. The present invention can obtain polymethyl methacrylate that has been decontaminated and dried by filtering, washing and drying.

[0057] In the present invention, Planck F-127, citric acid, a soluble cerium salt and a solvent are preferably mixed to obtain an impregnation solution.

[0058] In the present invention, the Planck F-127 is used as a soft template to improve the porosity of the precursor.

[0059] In the present invention, the citric acid provides an acidic environment.

[0060] In the present invention, the soluble cerium salt is preferably cerium nitrate. In the present invention, the soluble cerium salt provides a cerium source.

[0061] In the present invention, the mass ratio of Planck F-127, citric acid and soluble cerium salt is preferably (0.2-0.8): (0.5-1.5): (2-3), more preferably 0.5: 1: 2.5. The present invention controls the mass ratio of the three within the above range, which is more conducive to improving the porosity of the precursor.

[0062] In the present invention, the solvent is preferably a mixed solution of deionized water and ethanol, and the volume ratio of the deionized water to ethanol is preferably (1-2): (1-2), more preferably 1: 1. The use of the above solvent in the present invention is more conducive to dissolving each component.

[0063] In the present invention, the solvent serves as a dispersion medium for Planck F-127, citric acid and soluble cerium salt, and needs to be removed directly after subsequent immersion. Therefore, the present invention has no special limitation on the amount of the solvent, as long as it can fully dissolve Planck F-127, citric acid and soluble cerium salt.

[0064] The present invention has no particular limitation on the method of mixing the Planck F-127, citric acid, soluble cerium salt and solvent, as long as Planck F-127, citric acid and soluble cerium salt can be completely dissolved in the solvent.

[0065] After obtaining polymethyl methacrylate and the impregnation solution, the present invention preferably mixes the polymethyl methacrylate with the impregnation solution, and performs impregnation and drying in sequence to obtain a precursor.

[0066] In the present invention, the ratio of the mass of the polymethyl methacrylate to the volume of the impregnation solution is (2-5): (1-10), preferably 2: 5. In the present invention, since the polymethyl methacrylate needs to be removed during calcination, it can be adjusted as needed.

[0067] In the present invention, the impregnation temperature is preferably room temperature, and the impregnation time is preferably 1 to 8 hours, more preferably 3 to 5 hours. In the present invention, the impregnation is preferably carried out under stirring. The present invention has no particular limitation on the stirring speed, as long as the polymethyl methacrylate is in full contact with the impregnation liquid. The present invention can make the impregnation liquid fully distributed in the polymethyl methacrylate by impregnating under the above conditions.

[0068] In the present invention, the drying method is preferably to dry the solid-liquid mixture obtained by the impregnation in an oven. In an embodiment of the present invention, the drying temperature may be 60° C.; the drying time is preferably 8 to 12 hours, more preferably 10 to 12 hours. The present invention can remove the solvent by drying.

[0069] After obtaining the precursor, the present invention preferably calcines the precursor to obtain porous cerium dioxide.

[0070] In the present invention, the calcination preferably includes a first calcination and a second calcination performed sequentially. In an embodiment of the present invention, the calcination device may be a tube furnace.

[0071] In the present invention, the temperature of the first calcination is preferably 300-650°C, more preferably 600°C; the time of the first calcination is preferably 1-3 hours, more preferably 2-3 hours; the atmosphere of the first calcination is preferably nitrogen. The present invention can convert the cerium salt in the precursor into cerium dioxide by performing the first calcination under nitrogen.

[0072] In the present invention, the temperature of the second calcination is preferably 550-650°C, more preferably 600°C; the time of the second calcination is preferably 3-6h, more preferably 4-5h; the atmosphere of the second calcination is preferably oxygen. The present invention can remove polymethyl methacrylate and obtain three-dimensional ordered porous cerium dioxide by performing the second calcination under oxygen.

[0073] In the present invention, the molar percentage of the gold salt solution is preferably 0.1-1%, more preferably 0.5-1%. In the present invention, the gold salt solution is preferably a HAuCl4 aqueous solution. The present invention uses the above gold salt solution, which is more conducive to the gold salt solution obtaining uniformly distributed gold ions in the porous cerium dioxide.

[0074] In the present invention, when the molar percentage of the gold salt solution is 0.1-1%, the mass ratio of the porous cerium dioxide to the gold salt solution is preferably 0.1g:(0.01-0.1)g, more preferably 0.1g:0.05g. The present invention controls the amount of the two within the above range, which is more conducive to forming uniformly distributed gold ions in the porous cerium dioxide.

[0075] In the present invention, the reducing agent preferably includes one or more of calcium citrate, acetic acid and sodium citrate. The present invention uses a reducing agent to reduce gold ions to gold.

[0076] The present invention has no particular limitation on the amount of the reducing agent, as long as the amount can fully reduce the gold salt ions to gold element.

[0077] In the present invention, the method of mixing the porous cerium dioxide, the gold salt solution and the reducing agent is preferably as follows: after the porous cerium dioxide and the gold salt solution are uniformly mixed, the reducing agent solution is added to the mixed solution.

[0078] In the present invention, the temperature of the reduction reaction is preferably room temperature, and the time of the reduction reaction is preferably 0.1 to 3 hours, more preferably 1 to 2 hours. Under the above conditions, the present invention can make the gold ions react fully with the reducing agent to form gold.

[0079] In the present invention, the reduction reaction is preferably carried out under stirring. The present invention has no particular limitation on the rotation speed of the stirring, which can be adjusted as needed. The present invention is more conducive to the formation of gold fully dispersed on the surface and pores of the porous ceria by stirring.

[0080] The present invention preferably washes and dries the product of the reduction reaction in sequence to obtain a porous cerium dioxide / gold composite material. In the present invention, the washing is preferably centrifugal washing. In an embodiment of the present invention, the drying temperature may be 60° C., the drying time may be 12 hours, and the drying device may be an oven. The present invention can remove impurities by washing and drying.

[0081] After obtaining the porous cerium dioxide / gold composite material, the present invention mixes the porous cerium dioxide / gold composite material with a nickel salt solution to obtain a suspension.

[0082] In the present invention, the nickel salt solution is preferably a nickel chloride solution or a nickel acetate solution. The present invention can introduce nickel ions into the Prussian blue analogue by adding the nickel salt solution, thereby improving the catalytic activity of the catalyst.

[0083] In the present invention, the molar percentage of the nickel salt solution is preferably 10 to 90%, more preferably 50 to 70%. The present invention can make the nickel salt fully and evenly adsorbed in the porous cerium dioxide / gold composite material by mixing the porous cerium dioxide / gold composite material with the nickel salt solution, and affect the number of photocatalytic active sites. When the concentration of the nickel salt solution is within the above range, the catalytic activity of the catalyst is improved.

[0084] The present invention has no special limitation on the method of mixing the porous cerium dioxide / gold composite material with the nickel salt solution. A conventional mixing method can be used to uniformly mix the two.

[0085] The invention dissolves potassium cobalt cyanide and a surfactant in water to obtain a potassium cobalt cyanide mixed solution.

[0086] In the present invention, the potassium cobalt cyanide is used as a raw material for forming the framework structure of Prussian blue.

[0087] In the present invention, the surfactant preferably includes polyvinyl pyrrolidone, hexadecyl trimethyl ammonium chloride or sodium lauryl sulfate, and more preferably sodium lauryl sulfate. The present invention is more conducive to uniform mixing of the components by adding a surfactant.

[0088] In the present invention, the mass ratio of the potassium cobalt cyanide and the surfactant is preferably (0.7-3): (0.33-3). In an embodiment of the present invention, the mass ratio of the potassium cobalt cyanide and the surfactant can be 0.7:0.33, 2:1, 1:2, 3:2 or 2:3. The present invention controls the amount of the two within the above range, which is more conducive to improving the uniformity of each component, thereby improving the catalytic activity of the catalyst.

[0089] In the present invention, the water is preferably deionized water. The present invention uses water as a dispersion medium. In an embodiment of the present invention, when the mass of the potassium cobalt cyanide is 0.7 to 3 g, the volume of the water can be 20 mL.

[0090] The present invention has no particular limitation on the method of dissolving the potassium cobalt cyanide and the surfactant in water, as long as each component can be completely dissolved.

[0091] After obtaining the suspension and the potassium cobalt cyanide mixed solution, the present invention mixes the suspension with the potassium cobalt cyanide mixed solution and then performs an aging treatment to obtain an S-type heterojunction photocatalytic composite material.

[0092] In the present invention, the method for mixing the suspension with the potassium cobalt cyanide mixed solution is preferably to drop the potassium cobalt cyanide mixed solution into the suspension. The present invention preferably drips the potassium cobalt cyanide mixed solution in a microfluidic rate manner. In the present invention, the dripping rate is preferably 0.1 to 20 rpm, more preferably 1 to 10 rpm. The present invention is more conducive to fully mixing the product by dripping the potassium cobalt cyanide mixed solution in the above manner.

[0093] In the present invention, the temperature of the aging treatment is preferably room temperature, and the time of the aging treatment is preferably 1 to 24 hours, more preferably 3 to 6 hours. The aging treatment of the present invention is more conducive to forming a Prussian blue analogue with a more stable structure, and the formed Prussian blue analogue forms an S-type heterojunction with porous ceria and gold.

[0094] The present invention preferably washes and dries the product obtained after the aging treatment in sequence to obtain an S-type heterojunction photocatalytic composite material. In the present invention, the washing is preferably centrifugal washing. In an embodiment of the present invention, the drying temperature can be 60°C, the drying time can be 12 hours, and the drying device can be an oven.

[0095] The method provided by the invention can compound porous cerium dioxide, gold and Prussian blue analogs to form an S-type heterojunction.

[0096] The present invention also provides the use of the S-type heterojunction photocatalytic composite material described in the above technical solution as a biomass photorefining catalyst.

[0097] In the present invention, the biomass is preferably corn stalks. In the present invention, corn stalks are rich in cellulose, hemicellulose and lignin, and can be converted into high value-added chemicals and biofuels.

[0098] The present invention has no special limitation on the application method of the S-type heterojunction photocatalytic composite material as a biomass photorefining catalyst, and it can be used by a conventional catalyst application method.

[0099] The S-type heterojunction photocatalytic composite material provided by the present invention is an S-type heterojunction formed by a composite of porous cerium dioxide, gold and a Prussian blue analogue. The S-type heterostructured photocatalytic composite material not only retains the strong oxidizing ability of electrons and the strong reducing ability of holes, but also increases the contact area between the catalyst and the corn stalks during the photorefining process, while improving the distribution of the surface Brønsted acid sites, thereby greatly increasing the content of superoxide free radicals, thereby being more conducive to the photorefining of the corn stalks.

[0100] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0101] Example 1

[0102] An S-type heterojunction photocatalytic composite material, wherein the S-type heterojunction photocatalytic composite material is an S-type heterojunction formed by a composite of porous cerium dioxide, gold and a Prussian blue analogue;

[0103] The preparation method of the above-mentioned S-type heterojunction photocatalytic composite material is:

[0104] (1) The preparation method of porous cerium dioxide is:

[0105] 1) Water and methyl methacrylate (MMA) in a volume ratio of 2:1 were stirred at 80°C in an argon atmosphere to obtain a mixed solution, 0.3 g of potassium persulfate was quickly added to the mixed solution, and the mixture was stirred at 400 rmin. -1 The mixture was stirred at a speed of 1000 ℃ and the temperature was controlled to be 80℃ for polymerization reaction for 90 minutes; the product of the polymerization reaction was filtered with a filter paper with a diameter of 1 μm, and the filtrate was centrifuged and washed; the obtained solid was then dried in an oven at 60℃ for 12 hours to obtain polymethyl methacrylate;

[0106] 2) dissolving Planck F-127, citric acid and Ce(NO3)3 in a mass ratio of 0.5 g:1 g:2.5 g in a mixed solution of deionized water and ethanol in a volume ratio of 1:1 in 100 mL to obtain an impregnation solution;

[0107] 3) 2 g of the polymethyl methacrylate obtained in step 1) and the impregnation liquid obtained in step 2) are stirred and impregnated for 3 hours, and the solid-liquid mixture obtained after the impregnation is dried in an oven at 60° C. for 12 hours to obtain a precursor;

[0108] 4) placing the precursor obtained in step 3) in a tube furnace, performing a first calcination at 300° C. in a nitrogen atmosphere for 3 h, then changing the atmosphere to oxygen, performing a second calcination at 600° C. for 5 h, and obtaining three-dimensional ordered porous cerium dioxide.

[0109] After 0.1 g of the obtained three-dimensional ordered porous cerium dioxide and 0.5 mL of HAuCl4 aqueous solution with a molar percentage content were stirred evenly, a 1.5 g L -1 1.5 mL of sodium citrate was added to the mixed solution, and the mixture was stirred at room temperature for reduction reaction for 1 h. After centrifugation and washing, the mixture was dried in an oven at 60° C. for 12 h to obtain a porous cerium dioxide / gold composite material.

[0110] (2) stirring and mixing the porous cerium dioxide / gold composite material obtained in step (1) with a nickel chloride solution having a molar percentage content of 70% to obtain a suspension;

[0111] (3) dissolving potassium cobalt cyanide (K3[Co(CN)6]) and sodium dodecyl sulfate (SDS) in a mass ratio of 0.7 g:0.33 g in 20 mL of deionized water to obtain a potassium cobalt cyanide mixed solution;

[0112] (4) The potassium cobalt cyanide mixed solution obtained in step (3) is added dropwise to the suspension obtained in step (2) at a microfluidic rate of 10 rpm, and the mixture is aged at room temperature for 3 h. The obtained product is then centrifuged and washed, and dried in an oven at 60° C. for 12 h to obtain an S-type heterojunction photocatalytic composite material with a Prussian blue analog (PBA) concentration of 70%, which is named CeO2 / Au / 70%PBA.

[0113] Example 2

[0114] An S-type heterojunction photocatalytic composite material, wherein the S-type heterojunction photocatalytic composite material is an S-type heterojunction formed by a composite of porous cerium dioxide, gold and a Prussian blue analogue;

[0115] The preparation method of the above-mentioned S-type heterojunction photocatalytic composite material is:

[0116] (1) After 0.1 g of the three-dimensional ordered porous cerium dioxide obtained according to the method of Example 1 and 1.5 mL of a HAuCl4 aqueous solution with a molar content of 0.1% were stirred evenly, a 1.5 g L -11.5 mL of sodium citrate was added to the mixed solution, and the mixture was stirred at room temperature for reduction reaction for 1 h. After centrifugal washing, the mixture was dried in an oven at 60° C. for 12 h to obtain a porous cerium dioxide / gold composite material.

[0117] (2) stirring and mixing the porous cerium dioxide / gold composite material obtained in step (1) with a nickel chloride solution having a molar percentage content of 70% to obtain a suspension;

[0118] (3) dissolving K3[Co(CN)6] and SDS in a mass ratio of 2 g:1 g in 20 mL of deionized water to obtain a potassium cobalt cyanide mixed solution;

[0119] (4) The potassium cobalt cyanide mixed solution obtained in step (3) is added dropwise to the suspension obtained in step (2) at a microfluidic rate of 10 rpm, and the mixture is aged at room temperature for 3 h. The obtained product is then centrifuged and washed, and dried in an oven at 60° C. for 12 h to obtain an S-type heterojunction photocatalytic composite material with a PBA molar percentage of 70%, which is named CeO2 / Au / 70%PBA-2:1.

[0120] Example 3

[0121] An S-type heterojunction photocatalytic composite material, wherein the S-type heterojunction photocatalytic composite material is an S-type heterojunction formed by a composite of porous cerium dioxide, gold and a Prussian blue analogue;

[0122] The preparation method of the above-mentioned S-type heterojunction photocatalytic composite material is:

[0123] (1) After 0.1 g of the three-dimensional ordered porous cerium dioxide obtained according to the method of Example 1 and 1.5 mL of a HAuCl4 aqueous solution with a molar percentage of 0.1% were stirred evenly, a 1.5 g L -1 1.5 mL of sodium citrate was added to the mixed solution, and the mixture was stirred at room temperature for reduction reaction for 1 h. After centrifugal washing, the mixture was dried in an oven at 60° C. for 12 h to obtain a porous cerium dioxide / gold composite material.

[0124] (2) stirring and mixing the porous cerium dioxide / gold composite material obtained in step (1) with a nickel chloride solution having a molar percentage content of 70% to obtain a suspension;

[0125] (3) dissolving K3[Co(CN)6] and SDS in a mass ratio of 1 g:2 g in 20 mL of deionized water to obtain a potassium cobalt cyanide mixed solution;

[0126] (4) The potassium cobalt cyanide mixed solution obtained in step (3) is added dropwise to the suspension obtained in step (2) at a microfluidic rate of 10 rpm, and the mixture is aged at room temperature for 3 h. The obtained product is then centrifuged and washed, and dried in an oven at 60° C. for 12 h to obtain an S-type heterojunction photocatalytic composite material with a PBA molar percentage of 70%, which is named CeO2 / Au / 70%PBA-1:2.

[0127] Example 4

[0128] An S-type heterojunction photocatalytic composite material, wherein the S-type heterojunction photocatalytic composite material is an S-type heterojunction formed by a composite of porous cerium dioxide, gold and a Prussian blue analogue;

[0129] The preparation method of the above-mentioned S-type heterojunction photocatalytic composite material is:

[0130] (1) After 0.1 g of the three-dimensional ordered porous cerium dioxide obtained according to the method of Example 1 and 0.5 mL of a HAuCl4 aqueous solution with a molar content of 0.1% were stirred evenly, a 1.5 g L -1 1.5 mL of sodium citrate was added to the mixed solution, and the mixture was stirred at room temperature for reduction reaction for 1 h. After centrifugal washing, the mixture was dried in an oven at 60° C. for 12 h to obtain a porous cerium dioxide / gold composite material.

[0131] (2) stirring and mixing the porous cerium dioxide / gold composite material obtained in step (1) with a nickel chloride solution having a molar percentage content of 70% to obtain a suspension;

[0132] (3) dissolving K3[Co(CN)6] and SDS in a mass ratio of 3 g:2 g in 20 mL of deionized water to obtain a potassium cobalt cyanide mixed solution;

[0133] (4) The potassium cobalt cyanide mixed solution obtained in step (3) is added dropwise to the suspension obtained in step (2) at a microfluidic rate of 10 rpm, and the mixture is aged at room temperature for 3 h. The obtained product is then centrifuged and washed, and dried in an oven at 60° C. for 12 h to obtain an S-type heterojunction photocatalytic composite material with a PBA molar percentage of 70%, which is named CeO2 / Au / 70%PBA-3:2.

[0134] Example 5

[0135] An S-type heterojunction photocatalytic composite material, wherein the S-type heterojunction photocatalytic composite material is an S-type heterojunction formed by a composite of porous cerium dioxide, gold and a Prussian blue analogue;

[0136] The preparation method of the above-mentioned S-type heterojunction photocatalytic composite material is:

[0137] (1) After 0.1 g of the three-dimensional ordered porous cerium dioxide obtained according to the method of Example 1 and 0.5 mL of a HAuCl4 aqueous solution with a molar content of 0.1% were stirred evenly, a 1.5 g L -1 1.5 mL of sodium citrate was added to the mixed solution, and the mixture was stirred at room temperature for reduction reaction for 1 h. After centrifugation and washing, the mixture was dried in an oven at 60° C. for 12 h to obtain a porous cerium dioxide / gold composite material.

[0138] (2) stirring and mixing the porous cerium dioxide / gold composite material obtained in step (1) with a nickel chloride solution having a molar percentage content of 70% to obtain a suspension;

[0139] (3) dissolving K3[Co(CN)6] and SDS in a mass ratio of 2:3 in 20 mL of deionized water to obtain a potassium cobalt cyanide mixed solution;

[0140] (4) The potassium cobalt cyanide mixed solution obtained in step (3) is added dropwise to the suspension obtained in step (2) at a microfluidic rate of (0.1-20) rpm, and the mixture is aged at room temperature for 3 h. The obtained product is then centrifuged and washed, and dried in an oven at 60° C. for 12 h to obtain an S-type heterojunction photocatalytic composite material with a PBA concentration of 70%, which is named CeO2 / Au / 70%PBA-2:3.

[0141] Test Example 1

[0142] (1) The S-type heterojunction photocatalytic composite materials prepared in Examples 2 to 5 were tested using an X-ray diffractometer. The XRD patterns of the S-type heterojunction photocatalytic composite materials prepared in Examples 2 to 5 were as follows: Figure 1 As shown. Figure 1 It can be seen that the peak at θ=17.4° corresponds to the (200) crystal plane of PBA, the peak at θ=28.5° corresponds to the (220) crystal plane, and the peak at θ=36.2° corresponds to the (400) crystal plane, which indicates that CeO2, Au and PBA are successfully composited; the characteristic peaks of CeO2 / Au / PBA-2:1 and CeO2 / Au / PBA-3:2 belonging to PBA are located at the (200) crystal plane at θ=17.4° and the (220) crystal plane at θ=28.5°, and the characteristic peaks of CeO2 / Au / PBA-1:2 and CeO2 / Au / PBA-2:3 belonging to PBA are located at the (111) crystal plane at θ=14.8° and the (221) crystal plane at θ=23.7°. This shows that the mass ratio of K3[Co(CN)6] and SDS can precisely regulate the exposed crystal surface of CeO2 / Au / PBA, thereby regulating the catalytic efficiency of the photocatalyst.

[0143] (2) The S-type heterojunction photocatalytic composite materials obtained in comparative examples 2 to 5 were tested by scanning electron microscopy to obtain SEM images. From the SEM images, it can be seen that the three-dimensional ordered porous structures of CeO2 / Au / PBA-2:1, CeO2 / Au / PBA-3:2 and CeO2 / Au / PBA-2:3 all show spherical PBA accumulation on their surfaces, while the surface of CeO2 / Au / PBA-1:2 shows scattered lamellar accumulation, which indicates that the morphology of CeO2 / Au / PBA can change differently with the change of the mass ratio of K3[Co(CN)6] and SDS, and CeO2 / Au / PBA-2:1 with spherical accumulation on its surface is more conducive to the photorefining of corn straw.

[0144] (3) The CeO2, porous cerium dioxide / gold composite material (CeO2 / Au) and CeO2 / Au / 70% PBA prepared in step (1) of Example 1 were tested by UV-visible spectrophotometry. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the visible light absorption wavelength of CeO2 is 442nm and the band gap width is 2.53eV, and the visible light absorption wavelength of CeO2 / Au / 70%PBA is 464nm and the band gap width is 2.40eV. According to the calculation of the band gap width, valence band and conduction band, it can be confirmed that there is an S-type heterostructure between CeO2 / Au / PBA, which indicates the successful construction of the S-type heterojunction. Moreover, the heterojunction can effectively broaden the visible light absorption range of the photocatalytic material and shorten the band gap width, thus solving the problem that CeO2 cannot meet the requirements of the photocatalytic experiment due to its wide band gap.

[0145] (4) The S-type heterojunction photocatalytic composite material prepared in Example 1 was subjected to a NH3-programmed temperature desorption test to test the surface Bronsted acid sites of CeO2 / Au / 70% PBA. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that CeO2 / Au / 70%PBA has two Bronsted acidic peaks at 131°C and 252°C, respectively, and the peak at 252°C is more acidic. Therefore, it can be explained that there are abundant Bronsted acidic sites on the surface of CeO2 / Au / 70%PBA, which promote the photorefining of corn straw cellulose.

[0146] Example 6

[0147] A method for preparing an S-type heterojunction photocatalytic composite material is as follows:

[0148] (1) After 0.1 g of the three-dimensional ordered porous cerium dioxide obtained according to the method of Example 1 and 0.5 mL of a 1% HAuCl4 aqueous solution were stirred evenly, a 1.5 g L -11.5 mL of sodium citrate was added to the mixed solution, and the mixture was stirred at room temperature for reduction reaction for 1 h. After centrifugal washing, the mixture was dried in an oven at 60° C. for 12 h to obtain a porous cerium dioxide / gold composite material.

[0149] (2) stirring and mixing the porous cerium dioxide / gold composite material obtained in step (1) with a 10% nickel chloride solution to obtain a suspension;

[0150] (3) dissolving K3[Co(CN)6] and SDS in a mass ratio of 2:1 in 20 mL of deionized water to obtain a potassium cobalt cyanide mixed solution;

[0151] (4) The potassium cobalt cyanide mixed solution obtained in step (3) is added dropwise to the suspension obtained in step (2) at a microfluidic rate of 10 rpm, and the mixture is aged at room temperature for 3 h. The obtained product is then centrifuged and washed, and dried in an oven at 60° C. for 12 h to obtain an S-type heterojunction photocatalytic composite material with a PBA molar percentage of 10%, which is named CeO2 / Au / 10%PBA.

[0152] Example 7

[0153] The difference from Example 6 is that in step (2): the porous cerium dioxide / gold composite material obtained in step (1) is stirred and mixed with a nickel chloride solution having a molar percentage content of 30% to obtain a suspension;

[0154] The remaining steps are the same as those in Example 6, and an S-type heterojunction photocatalytic composite material with a PBA molar percentage of 30% is obtained, which is named CeO2 / Au / 30%PBA.

[0155] Example 8

[0156] The difference from Example 6 is that in step (2): the porous cerium dioxide / gold composite material obtained in step (1) is stirred and mixed with a nickel chloride solution having a concentration of 50% to obtain a suspension;

[0157] The remaining steps are the same as those in Example 6, and an S-type heterojunction photocatalytic composite material with a PBA molar percentage of 50% is obtained, which is named CeO2 / Au / 50%PBA.

[0158] Example 9

[0159] The difference from Example 6 is that in step (2): the porous cerium dioxide / gold composite material obtained in step (1) is stirred and mixed with a nickel chloride solution having a molar percentage content of 70% to obtain a suspension;

[0160] The remaining steps are the same as those in Example 6, and an S-type heterojunction photocatalytic composite material with a PBA molar percentage of 70% is obtained, which is named CeO2 / Au / 70%PBA.

[0161] Example 10

[0162] The difference from Example 6 is that in step (2): the porous cerium dioxide / gold composite material obtained in step (1) is stirred and mixed with a nickel chloride solution having a molar percentage content of 90% to obtain a suspension;

[0163] The remaining steps are the same as those in Example 6, and an S-type heterojunction photocatalytic composite material with a PBA molar percentage of 90% is obtained, which is named CeO2 / Au / 90%PBA.

[0164] Comparative Example 1

[0165] A method for preparing a photocatalytic material is to obtain three-dimensional ordered porous cerium dioxide according to the method of Example 1, and named it CeO2.

[0166] Application Example 1

[0167] The S-type heterojunction photocatalytic composite materials prepared in Examples 1, 6 to 10 and the S-type heterojunction photocatalytic material prepared in Comparative Example 1 were subjected to a photorefining corn stalk experiment, and the specific process is as follows:

[0168] (1) 20 mg of the photocatalytic composite material and 100 mg of corn stalks were placed in a stainless steel reactor (100 mL) with a quartz window on the top, 50 mL of H2O and 4 wt% NaOH were added into the reactor, and stirred to form a uniform mixed solution;

[0169] (2) injecting O2 gas into the reactor until the pressure rises to 1 MPa;

[0170] (3) Use 300W Xe lamp as the light source, the light intensity is 150mW cm -2 The gaseous products were analyzed by gas chromatography and flame ionization detector (FID).

[0171] The gas product analysis results obtained in this application example are as follows:

[0172] The XRD patterns of the samples (CeO2 / Au / PBA) and (CeO2 / Au) prepared in Example 1 and CeO2 prepared in Comparative Example 1 are shown in FIG. Figure 4 The XRD patterns of the samples obtained in Examples 6 to 10 and Comparative Example 1 are shown in Figure 5 As shown, through Figure 5It can be found that with the increase of PBA concentration, the peaks of (200) crystal plane of PBA at θ=17.4°, (220) crystal plane at θ=28.5° and (400) crystal plane at θ=36.2° gradually increase, which indicates that CeO2, Au and PBA are successfully composited. The SEM spectrum of the sample obtained in Example 1 is as follows: Figure 6 As shown, CeO2 / Au / 10% PBA, CeO2 / Au / 30% PBA, CeO2 / Au / 50% PBA, CeO2 / Au / 70% PBA, CeO2 / Au / 90% PBA and CeO2 all present a three-dimensional ordered porous structure with an average pore size of about 100nm. The surface of CeO2 is very smooth, without the accumulation of other substances. As the concentration of Prussian blue increases, the surface of CeO2 gradually becomes rough, forming an accumulation of Prussian blue layers, and it can be observed that the thickness of the Prussian blue layer becomes thicker as the concentration of Prussian blue increases. By comparing the BET characterization of the samples obtained in Example 1 and Comparative Example 1, it is found that the specific surface area of ​​CeO2 is 34.48m 2 g -1 The specific surface area of ​​CeO2 / Au / 70%PBA is 66.94m 2 g -1 , which shows that the three-dimensional ordered porous structure can increase the surface area of ​​CeO2, which is beneficial to the adsorption of corn stalks and further enhances its ability to photo-refine corn stalks. By comparing the UV-vis characterization of the samples obtained in Example 1 and Comparative Example 1, it was found that the visible light absorption wavelength of CeO2 was 442nm and the band gap width was 2.53eV, and the visible light absorption wavelength of CeO2 / Au / 70%PBA was 464nm and the band gap width was 2.40eV, which shows that the S-type heterojunction was successfully constructed, and the heterojunction can effectively broaden the visible light absorption range of the photocatalytic material and shorten the band gap width, solving the problem that CeO2 cannot meet the requirements of the photocatalytic experiment due to its wide band gap. The yield of formic acid generated by CeO2 / Au / 10%PBA is 11.51mmol L -1 The reaction rate of generating CO is 0.76 mmol g -1 The yield of formic acid generated by CeO2 / Au / 30%PBA was 10.82mmol L -1 The reaction rate of generating CO is 0.58 mmol g -1 The yield of formic acid generated by CeO2 / Au / 50%PBA was 17.08mmol L -1 The reaction rate of CO generation is 1.03 mmol g -1 cat; CeO2 / Au / 7%PBA produces formic acid with a yield of 19.6 mmol L -1 The reaction rate of generating CO is 1.56 mmol g-1 The yield of formic acid generated by CeO2 / Au / 90%PBA was 15.55mmol L -1 The reaction rate of generating CO is 0.73 mmol g -1 The results show that the concentration of PBA determines the metal ratio of CeO2 / Au / PBA photocatalytic composite materials, and the change of metal ratio determines the number of photocatalytic active sites. The appropriate addition of PBA (70%) can form an S-type heterostructure, which is more suitable for the reaction of photorefined corn straw and improves the conversion rate of photorefined corn straw into high value-added platform compounds.

[0173] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An S-type heterojunction photocatalytic composite material, wherein the S-type heterojunction photocatalytic composite material is an S-type heterojunction formed by a composite of porous cerium dioxide, gold and a Prussian blue analogue.

2. The method for preparing the S-type heterojunction photocatalytic composite material according to claim 1, comprising the following steps: (1) mixing porous cerium dioxide, a gold salt solution and a reducing agent, and performing a reduction reaction to obtain a porous cerium dioxide / gold composite material; (2) mixing the porous cerium dioxide / gold composite material obtained in step (1) with a nickel salt solution to obtain a suspension; (3) dissolving potassium cobalt cyanide and a surfactant in water to obtain a potassium cobalt cyanide mixed solution; (4) The suspension obtained in step (2) is mixed with the potassium cobalt cyanide mixed solution obtained in step (3), and then subjected to aging treatment to obtain an S-type heterojunction photocatalytic composite material.

3. The preparation method according to claim 2, characterized in that: The method for preparing porous cerium dioxide in step (1) comprises: 1) mixing water, methyl methacrylate and an initiator to carry out a polymerization reaction to obtain polymethyl methacrylate; 2) mixing Planck F-127, citric acid, a soluble cerium salt and a solvent to obtain an impregnation solution; 3) mixing the polymethyl methacrylate obtained in step 1) with the impregnation solution obtained in step 2), and sequentially performing impregnation and drying to obtain a precursor; 4) calcining the precursor obtained in step 3) to obtain porous cerium dioxide.

4. The preparation method according to claim 2, characterized in that: The molar percentage of the gold salt solution in step (1) is 0.1-1%.

5. The preparation method according to claim 2, characterized in that: The temperature of the reduction reaction in step (1) is room temperature, and the time of the reduction reaction is 0.5 to 3 hours.

6. The preparation method according to claim 2, characterized in that: The molar percentage of the nickel salt solution in step (2) is 10-90%.

7. The preparation method according to claim 2, characterized in that: In the step (3), the mass ratio of potassium cobalt cyanide to surfactant is (0.1-3): (0.2-3).

8. The preparation method according to claim 2, characterized in that: The temperature of the aging treatment in step (4) is room temperature.

9. The preparation method according to claim 2 or 8, characterized in that: The aging treatment time is 1 to 24 hours.

10. Use of the S-type heterojunction photocatalytic composite material according to claim 1 or the S-type heterojunction photocatalytic composite material prepared by the preparation method according to any one of claims 2 to 9 as a biomass photorefining catalyst.